Measuring fluoride concentration in mineral waters in the Araraquara region, Brazil - Brandão, Ioneide Maria Gomes [UNESP]; Valsecki Junior, Aylton [UNESP] (FapUNIFESP (SciELO), 1998)
It has been shown that people of all ages can benefit from the topical and systemic effects of water fluoridation. However, the increase in consumption of bottled water, either to substitute for or supplement consumption of water from public sources, has implications for safe fluoride supplementation. Taking that into consideration, in 1995 we analyzed the fluoride content in 31 commercial brands of mineral water in the region of Araraquara, state of Sao Paulo, Brazil. Fluoride concentration as determined by our analysis was compared to the concentration of fluoride specified on each label. Only 25% of the products studied listed the fluoride concentration on their labels. In addition, among 31 mineral water brands, 26 listed the date when the chemical analysis to determine chemical composition had been performed. Of these, 20 had not been put through the annual chemical analysis determined by Brazilian law. Based on these results, if the mineral waters tested had been the only source of drinking water, fluoride supplementation would have been necessary in 69% of the samples analyzed. In the case of children up to 6 years of age who use products containing fluoride, such as topical gels, mouthwashes or toothpastes, supplementation should be recommended only if commercially bottled water is the only source of water used, not only for drinking but for cooking as well.
Keywords: drinking water; mineral water; fluoride; toothpaste; water quality; brazil; chemical composition; cooking; fluid intake; water analysis; child; fluoridation; human; preschool child; Brazil; Child; Child, Preschool; Dentifrices; Fluoridation; Fluorides; Humans; Mineral Waters